2015
DOI: 10.1371/journal.ppat.1004841
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Infection and Commensal Microbiota Drive Early IL-10 Production in the Skin by CD4+ T Cells That Are Functionally Suppressive

Abstract: The skin provides an important first line of defence and immunological barrier to invasive pathogens, but immune responses must also be regulated to maintain barrier function and ensure tolerance of skin surface commensal organisms. In schistosomiasis-endemic regions, populations can experience repeated percutaneous exposure to schistosome larvae, however little is known about how repeated exposure to pathogens affects immune regulation in the skin. Here, using a murine model of repeated infection with Schisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 79 publications
2
25
0
1
Order By: Relevance
“…On the other hand, CD4+GATA‐3+ (~Th2) proportion in the DLN for periphery and especially CD4+Foxp3+ (~Treg) cells in all observed lymphoid organs appeared to be increased suggesting they might contribute to IL‐10 production. As for Tregs, it is in contrast with their unchanged presence in the periphery DLN or spleen in early Schistosoma mansoni infection 28‐30 . Here, IL‐10 is produced by CD4+ T cells, 30 specifically Th2 28 or dermal dendritic cells 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, CD4+GATA‐3+ (~Th2) proportion in the DLN for periphery and especially CD4+Foxp3+ (~Treg) cells in all observed lymphoid organs appeared to be increased suggesting they might contribute to IL‐10 production. As for Tregs, it is in contrast with their unchanged presence in the periphery DLN or spleen in early Schistosoma mansoni infection 28‐30 . Here, IL‐10 is produced by CD4+ T cells, 30 specifically Th2 28 or dermal dendritic cells 31 .…”
Section: Discussionmentioning
confidence: 99%
“…As for Tregs, it is in contrast with their unchanged presence in the periphery DLN or spleen in early Schistosoma mansoni infection 28‐30 . Here, IL‐10 is produced by CD4+ T cells, 30 specifically Th2 28 or dermal dendritic cells 31 . The regulatory milieu might be induced, among others, by skin commensal bacteria 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, it is perhaps surprising that we did not detect a significant reduction in IL‐10 cytokine production in the absence of eosinophils. However, we recently showed that in 4x schistosome‐infected mice, the majority of IL‐10 + cells in the skin were of lymphoid, rather than myeloid, origin . Thus, eosinophils are not a source of regulatory IL‐10 in our model despite their abundance.…”
Section: Discussionmentioning
confidence: 73%
“…4), supporting the postulate that HdAg directly drove a unique, and putatively M reg phenotype. [The possibility that some gene changes were due to the trace levels of LPS contamination of the HdAg or the combined effect of helminth and microbe products cannot be excluded (52). ] Identification of the molecules in the HdAg that affects macrophage gene transcription and function ( i.e ., suppressed response to LPS) is important and will require extensive research efforts.…”
Section: Discussionmentioning
confidence: 99%